The role of arbuscular mycorrhizal fungi in abiotic stress management in viticulture under climatic shifts - Brenda Valenzuela-Aragon; Massimiliano Cardinale; Eleonora Rolli; Laura Rustioni; Davide Francioli (Plant Stress)
Arbuscular mycorrhizal fungi (AMF) have been shown to enhance grapevine resilience to abiotic stresses, which are becoming increasingly severe due to climate change. Grapevines, which are central to global wine production, face critical challenges such as drought, salinity, extreme temperatures, and soil degradation. These challenges have the potential to compromise yield, quality, and economic sustainability. AMF establish symbiotic relationships with grapevine roots, thereby improving nutrient and water uptake, enhancing photosynthetic efficiency, and modulating stress-related pathways. These fungi also promote soil health by increasing microbial diversity, stabilizing soil structure, and reducing the need for chemical inputs. The application of AMF inoculants in viticulture presents substantial opportunities, including improved grapevine adaptation to environmental stresses, higher fruit quality, and reduced environmental impact. However, challenges such as ensuring consistent performance across diverse environmental conditions, optimizing inoculant formulations, and addressing vineyard management practices that may reduce AMF effectiveness must be overcome to maximize their benefits. Advances in precision agriculture and research into AMF-host interactions are essential to unlocking their full potential. This review explores the mechanisms by which AMF mitigate abiotic stress, the benefits of their integration into vineyard management, and the challenges that must be overcome to implement AMF-based solutions.